Introduction: modern Tamil Saivism and Saiva Siddhanta - Klöber, Rafael (Journal of Hindu studies, 2017)
© The Author 2017. Oxford University Press and The Oxford Centre for Hindu Studies. All rights reserved. For permissions, please email journals.permissionsoup.comTamil Saivism (caivam, caiva camayam)1 is a worldwide reality at the beginning of the twenty-first century. Expressions of Tamil Saivism can not only be found in South India and Sri Lanka, but also all across the globe in Tamil-speaking communities. There exist numerous organizations for the spread of Tamil Saivism and its supposed ‘core philosophy’ Saiva Siddhanta (caiva cittāntam, Skt. śaiva siddhānta) in South India, South-East Asia, Europe, South Africa, and North America. Their advocates situate themselves decidedly within a broader tradition called ‘Hinduism’ and even assert that they are its only true and universal heir. However, Tamil Saivism and Saiva Siddhanta and their controversial claims hardly feature in the scholarly and religious discourse on Hinduism (a highly contested term itself, of...